Development of the adverse outcome pathway "alkylation of DNA in male premeiotic germ cells leading to heritable mutations" using the OECD's users' handbook supplement - Yauk, Carole L.; Lambert, Iain B.; Meek, M.E. (Bette); Douglas, George R.; Marchetti, Francesco (Environmental and molecular mutagenesis, 2015)
The Organisation for Economic Cooperation and Development's (OECD) Adverse Outcome Pathway (AOP) programme aims to develop a knowledgebase of all known pathways of toxicity that lead to adverse effects in humans and ecosystems. A Users' Handbook was recently released to provide supplementary guidance on AOP development. This article describes one AOP—alkylation of DNA in male premeiotic germ cells leading to heritable mutations. This outcome is an important regulatory endpoint. The AOP describes the biological plausibility and empirical evidence supporting that compounds capable of alkylating DNA cause germ cell mutations and subsequent mutations in the offspring of exposed males. Alkyl adducts are subject to DNA repair; however, at high doses the repair machinery becomes saturated. Lack of repair leads to replication of alkylated DNA and ensuing mutations in male premeiotic germ cells. Mutations that do not impair spermatogenesis persist and eventually are present in mature sperm. Thus, the mutations are transmitted to the offspring. Although there are some gaps in empirical support and evidence for essentiality of the key events for certain aspects of this AOP, the overall AOP is generally accepted as dogma and applies broadly to any species that produces sperm. The AOP was developed and used in an iterative process to test and refine the Users' Handbook, and is one of the first publicly available AOPs. It is our hope that this AOP will be leveraged to develop other AOPs in this field to advance method development, computational models to predict germ cell effects, and integrated testing strategies. Environ. Mol. Mutagen. 56:724–750, 2015. © 2015 Her Majesty the Queen in Right of Canada.